Socio-economic burden of sickle cell disease on families attending sickle cell clinic in Kano state, northwestern Nigeria - I.I. Beli; L.A. Ali; C.C. Onuoha; M. Jasseh; M. Zentar; N. Belakoul; Y. Layadi; J.A. Deblui; M. Fathi; A.H. Sani; A.G. Adamu; M.A. Mbahi; et al. (Elsevier, 2024)
This study aimed to assess the socio-economic impact of sickle cell disease (SCD) on families of patients receiving care at the SCD clinic of Aminu Kano Teaching Hospital (AKTH) in Kano, Northwest Nigeria. The research adopted a descriptive cross-sectional approach, involving the participation of 273 individuals selected through a multi-stage sampling method. Data was gathered using semi-structured interviews and subjected to analysis using SPSS software. The study achieved a 100 % response rate, with 84 % of the participants being females. The average age of the participants was 35.1 ± 8.6 years, and a significant proportion (79.9 %) reported a monthly income of thirty thousand naira or less. The findings of the study revealed that SCD had a notable social impact, affecting 93.5 % of participants occasionally and 5.8 % most of the time. Furthermore, a substantial financial burden was experienced by 54.2 % of respondents most of the time and 45.1 % occasionally. The research also highlighted the significant influence of SCD on guardians' employment status, income levels, time spent in hospitals, medical expenditures, and overall quality of life. These findings underscore the considerable social and financial challenges faced by guardians of SCD patients. Study results supports prioritizing affordable healthcare access for families affected by SCD to alleviate the burdens they face.